Spatiotemporal patterns of carbon emissions and carbon balance zoning in Inner Mongolia based on land use change - Meng, Jianwei; Zhan, Huixin; Tang, Bing; Zhang, Hongli; Lin, Yinghua (Frontiers in Environmental Science, 2025)
Under the background of “dual carbon”, Taking the Inner Mongolia Autonomous Region as the research area, based on land use data and local economic data, were used to measure the land use change and carbon emission of the research area from 2000 to 2024, The carbon balance of various cities in Inner Mongolia is zoned and to provide a basis and support for the optimization of territorial space. [Result](1) During the period, the land use dynamics of forest land, construction land and wetland increased, while the changes in the areas of farmland, grassland, water area and unused land decreased. (2) The total carbon emissions of construction land and cultivated land in Inner Mongolia showed an upward trend. The total amount of carbon absorption rose slightly. (3) The total net carbon emissions in 2024 increase by approximately 133% compared to 2000. In terms of carbon budget balance, Hulunbuir City was in a state of carbon balance from 2000 to 2015, but after 2015, all prefecture-level cities have been in an unbalanced state where carbon emissions exceed carbon absorption. (4) The economic contribution rate of carbon emissions in various cities of Inner Mongolia shows significant differences. The cities with an ecological carrying coefficient greater than 1 are Alxa League and Hulun Buir City. (5) Based on the carbon balance analysis, Inner Mongolia are divided into low-carbon development zones, low-carbon economic zones, low-carbon maintenance zones, economic development zones, carbon intensity control zones, and high-carbon optimization zones. The value of this research demonstrates that arid and semi-arid regions can achieve the synergy of ecological protection, economic development, and carbon reduction through land-use optimization. It provides a scientific approach for similar regions to resolve the conflict between development and emission reduction, and it is of great significance for the implementation of the national “dual-carbon” strategy, the construction of ecological security barriers in northern China, and the study of carbon cycles in global arid areas.